Analysis of a model for bacteriophage infections and bacteria defense: a synergetics perspective - Frank, T. D. (Frontiers in Network Physiology, 2025)
A model for bacteriophage infections and bacteria defense is analyzed using the concepts of synergetics. The model order parameter is determined and the corresponding amplitude equations are derived. Within this framework it is shown how the order parameter defines a multi-species building block that captures the organization of infection outbreaks and the initial defense reaction and how the order parameter amplitude determines the corresponding temporal characteristics. Two approximative models with different domains of application are derived as well. In doing so, a supplementary perspective of bacteriophage infections that provides insights beyond the classical state space perspective is provided.